Aspirin‐intolerant asthma in the population: prevalence and important determinants. Issue 1 (January 2015) - Eriksson, J.; Ekerljung, L.; Bossios, A.; Bjerg, A.; Wennergren, G.; Rönmark, E.; Torén, K.; Lötvall, J.; Lundbäck, B.
Summary Background Population‐based studies on aspirin‐intolerant asthma (AIA) are very few, and no previous population study has investigated risk factors for the condition. Objective To investigate the prevalence and risk factors of AIA in the general population. Methods A questionnaire on respiratory health was mailed to 30 000 randomly selected subjects aged 16–75 years in West Sweden, 29 218 could be traced and 18 087 (62%) responded. The questionnaire included questions on asthma, respiratory symptoms, aspirin‐induced dyspnoea and possible determinants. Results The prevalence of AIA was 0.5%, 0.3% in men and 0.6% in women (P = 0.014). Sick leave, emergency visits due to asthma and all investigated lower respiratory symptoms were more common in AIA than in aspirin‐tolerant asthma (ATA). Obesity was a strong risk factor for AIA (BMI > 35: odds ratio (OR) 12.1; 95% CI 2.49–58.5), and there was a dose‐response relationship between increasing body mass index (BMI) and risk of AIA. Obesity, airborne occupational exposure and visible mould at home were considerably stronger risk factors for AIA than for ATA. Current smoking was a risk factor for AIA (OR 2.55; 95% CI 1.47–4.42), but not ATA. Conclusion Aspirin‐intolerant asthma identified in the general population was associated with a high burden of symptoms, uncontrolled disease and a high morbidity. Increasing BMI increased the risk of AIA in a dose‐response manner. A number of risk factors, including obesity and current smoking, were considerably stronger for AIA than for ATA.